Stephen of Pisa and Antioch : Liber Mamonis : An Introduction to Ptolemaic Cosmology and Astronomy from the Early Crusader States /: Liber Mamonis : An Introduction to Ptolemaic Cosmology and Astronomy from the Early Crusader States. ([2019]) - Grupe, Dirk
No abstract available